1976
DOI: 10.1111/j.1651-2227.1976.tb04899.x
|View full text |Cite
|
Sign up to set email alerts
|

NEONATAL HYPERTRIGLYCERIDEMIA A New Index of Antepartum‐Intrapartum Fetal Stress?

Abstract: The 95th percentile value of cord serum triglyceride concentration in 82 consecutively live born infants was found to be 0.79 mmol/l. This level was arbitrarily used to define neonatal hypertriglyceridemia. A comparison between 78 normotriglyceridemic and 61 hypertriglyceridemic newborn infants showed a significant association between elevated cord serum triglyceride concentration and insufficiency of the placenta, fetal bradycardia, meconium-stained amniotic fluid and one-minute Apgar score less than or equal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

1977
1977
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(12 citation statements)
references
References 16 publications
2
10
0
Order By: Relevance
“…This was in unison with few other studies including Anderson et al and Tsang et al which showed no significant changes in the cord blood lipid profile in terms of gender. 12,13 But contrasting results were noted in studies by Hardell et al, Zhao et al, Simmi Kharb et al and Badiee Z et al who noted significantly higher total cholesterol and HDL levels in their study group. [14][15][16][17] Higher and statistically significant values of total cholesterol, LDL and triglyceride levels were noted in our low birth weight (LBW) study group.…”
Section: Resultsmentioning
confidence: 38%
“…This was in unison with few other studies including Anderson et al and Tsang et al which showed no significant changes in the cord blood lipid profile in terms of gender. 12,13 But contrasting results were noted in studies by Hardell et al, Zhao et al, Simmi Kharb et al and Badiee Z et al who noted significantly higher total cholesterol and HDL levels in their study group. [14][15][16][17] Higher and statistically significant values of total cholesterol, LDL and triglyceride levels were noted in our low birth weight (LBW) study group.…”
Section: Resultsmentioning
confidence: 38%
“…Several investigators have shown that prenatal and perinatal complications can influence CB lipid levels (12)(13)(14)(15)(16)(17)(18)(19)(20). It is well known that prematurity (gestational age less than 37 wk) is associated with elevated TC and low TG (1 2, 14, 17-19, 2 1) and that TC is elevated in infants of diabetic mothers (19,35,36).…”
Section: Discussionmentioning
confidence: 99%
“…Of the total CB plasmas examined, 154 samples with plasma volume of 2 ml or more were selected for determination of HDL-cholesterol and for evaluation by gradient polyacrylamide gel electrophoresis. Since prematurity and perinatal complications have been shown to be associated with elevated CB lipid levels (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22), emphasis was placed on inclusion of infants with pre-and perinatal complications or lipid levels above 100 mg/dl.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3] Concentrations of the cord blood lipoprotein subtypes are influenced by fetal malnutrition and prematurity. [4][5][6] High concentrations of triglyceride-rich lipoproteins, and apolipoprotein B in infants with a low gestational age; and increase of Apo c-1 rich in high-density lipoprotein (HDL) with low birth weight are potential risk factors for cardiovascular disease in the future.…”
Section: Introductionmentioning
confidence: 99%